Knowledge and attitude towards childhood immunisation among parents in Lahad Datu, Sabah. - Amin, Lina Syafiqah (Universiti Sains Malaysia, 2024)
In today's competitive world, nursing students face high-stress levels due to their demanding studies and continuous examinations. The clinical component also adds to the stress. Thus, good time management can reduce their stress level. This study aimed to determine the time management skills and stress levels among undergraduate nursing students at Universiti Sains Malaysia (USM). A cross-sectional study was conducted using an online survey among 116 nursing students selected via a simple random method between January 2024 to February 2024. The survey instruments consisted of socio-demographic characteristics, 27 items on the Time Management Inventory and 22 items on the Student Nursing Stress Index. Data were analyzed using Statistical Package Social Sciences version 28.0 software. Descriptive statistics, One-Way Analysis of Variance and Pearson Chi-square tests were conducted. Findings revealed that 82.8% of participants had moderate time management skills, while 5.2% had low skills, and only 12.1% had high time management skills. Of the total participants, 19.8% experienced low stress levels, 80.0% experienced moderate stress, and 11.2% experienced high stress. While age, gender, ethnicity, year of study, and Cumulative Grade Point Average (CGPA) have no significant association with time management skills and stress levels. However, time management skills were significantly associated with stress levels (p=0.006). This study concludes that nursing students have moderate time management skills and moderate stress levels, with time management skills being significantly associated with stress levels, suggesting the need for intervention programs to improve these skills.